Biomedical nanoparticle design: What we can learn from viruses - Maslanka Figueroa, Sara (J Control Release, 2021)
Viruses are nanomaterials with a number of properties that surpass those of many synthetic nanoparticles (NPs) for biomedical applications. They possess a rigorously ordered structure, come in a variety of shapes, and present unique surface elements, such as spikes. These attributes facilitate propitious biodistribution, the crossing of complex biological barriers and a minutely coordinated interaction with cells. Due to the orchestrated sequence of interactions of their stringently arranged particle corona with cellular surface receptors they effectively identify and infect their host cells with utmost specificity, while evading the immune system at the same time. Furthermore, their efficacy is enhanced by their response to stimuli and the ability to spread from cell to cell. Over the years, great efforts have been made to mimic distinct viral traits to improve biomedical nanomaterial performance. However, a closer look at the literature reveals that no comprehensive evaluation of the benefit of virus-mimetic material design on the targeting efficiency of nanomaterials exists. In this review we, therefore, elucidate the impact that viral properties had on fundamental advances in outfitting nanomaterials with the ability to interact specifically with their target cells. We give a comprehensive overview of the diverse design strategies and identify critical steps on the way to reducing them to practice. More so, we discuss the advantages and future perspectives of a virus-mimetic nanomaterial design and try to elucidate if viral mimicry holds the key for better NP targeting.